1993
DOI: 10.1136/hrt.69.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of ventricular response to atrial flutter after intravenous adenosine.

Abstract: Adenosine may be of therapeutic and diagnostic value in the emergency management of arrhythmias. It causes transient atrioventricular nodal block and thus ends paroxysmal supraventricular tachycardias that involve the atrioventricular node. Also, it may uncover underlying atrial arrhythmias by slowing the ventricular response. Its duration of action is brief and serious adverse effects have not been reported. A 12 year old patient with atrial flutter is presented, in whom intravenous adenosine was followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Some authors reported also a dangerous increase of the ventricular rate in atrial flutter patients following the administration of adenosine, with conduction increasing from 2:1 to 1:1 after a brief period of high grade atrioventricular block [11][12][13]. Three of these five reported cases required electrical cardioversion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors reported also a dangerous increase of the ventricular rate in atrial flutter patients following the administration of adenosine, with conduction increasing from 2:1 to 1:1 after a brief period of high grade atrioventricular block [11][12][13]. Three of these five reported cases required electrical cardioversion.…”
Section: Discussionmentioning
confidence: 99%
“…Because the signal transduction pathways activated by adenosine and acetylcholine converge on the same potassium channels to produce similar electrophysiologic effects in the atrial myocardium, adenosine induced and vagus nerve-dependent AF are mechanistically similar. Both adenosine and vagus nerve activation cause spatially and temporally heterogeneous shortening of atrial refractoriness [10].Some authors reported also a dangerous increase of the ventricular rate in atrial flutter patients following the administration of adenosine, with conduction increasing from 2:1 to 1:1 after a brief period of high grade atrioventricular block [11][12][13]. Three of these five reported cases required electrical cardioversion.…”
mentioning
confidence: 99%
“…[11][12][13] A similar response has been described in atrial flutter. [14][15][16] This ''rebound'' phenomenon may result from an increase in sympathetic nerve activity and plasma catecholamine levels. 11 Adenosine induced ventricular arrhythmias including ventricular tachycardia, 17 polymorphic ventricular tachycardia, [18][19][20][21] and ventricular fibrillation 22 have all been described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…2 In this situation, the most dreaded consequence is degeneration of the arrhythmia into ventricular flutter or fibrillation and cardiac arrest. 3 We report an adverse event in a patient who received adenosine in an attempt to clarify the etiology of a supraventricular tachycardia.…”
Section: To the Editormentioning
confidence: 99%
“…2 In this situation, the most dreaded consequence is degeneration of the arrhythmia into ventricular flutter or fibrillation and cardiac arrest. 3 We report an adverse event in a patient who received adenosine in an attempt to clarify the etiology of a supraventricular tachycardia.A 77 year old female with a history of rheumatoid arthritis presented to our institution complaining of profound fatigue for one day. Her electrolytes, complete blood count, TSH and serial troponins were all within normal limits.…”
mentioning
confidence: 99%